Effects of Bilateral Transcranial Direct Current Stimulation on Simultaneous Bimanual Handgrip Strength - Hikosaka, Mikito; Aramaki, Yu (Frontiers in Human Neuroscience, 2021)
Although the effects of transcranial direct current stimulation (tDCS) on contralateral unimanual movement have been well reported, its effects on coordinated multi-limb movements remain unclear. Because multi-limb coordination is often performed in daily activities and sports, clarifying the effects of tDCS on multi-limb coordination may have valuable implications. However, considering the neural crosstalk involved in bimanual movements, including the transcallosal pathway and ipsilateral motor pathway, the extent of tDCS-induced improvement may differ between unimanual and bimanual movement. We examined how tDCS affects simultaneous bimanual maximal voluntary contraction by testing the effects of tDCS of bilateral primary motor cortex (M1) on unimanual and bimanual handgrip strength. Twenty-one right-handed healthy adults underwent three bilateral tDCS protocols (“RaLc,” with an anode on right M1 and a cathode on left M1, “RcLa,” with an anode on left M1 and a cathode on right M1, and “Sham”) in a randomized order. A 1.5 mA current was applied for 15 min during tDCS. Participants then performed maximal unimanual and bimanual handgrip tests. Bimanual handgrip force was higher in both hands in the RcLa condition than in the Sham condition. Similarly, unimanual handgrip force was higher in the RcLa condition than in the Sham condition. Stimulus responses were asymmetrical and were not observed in the RaLc condition. Our findings demonstrate that RcLa tDCS leads to neuromodulation that can produce greater unimanual and bimanual handgrip strength. This result provides basic evidence that tDCS may be useful in sports, particularly those involving bilateral coordination of upper limb movement.